PENDIDIKAN ISLAM DAN BAHASA ARAB MULTIKULTURAL DI MADRASAH - Rifa'i, Ahmad (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Multicultural education means to learn about, prepare for, and celebrate cultural diversity. It requires changes in school programs, policies and practices. Experts agreed that the content, structure and specific practices in multicultural education are different according to the settings. This article will focus its discussion on multural education in teaching Arabic language. It found that multicultural education in teaching and learning Arabic language can be implemented in maḥārah al-arbā’, including learning maḥārah qirā’ah, mahārah kalām, mahārah kitābah, and mahārah istimā’. In globalization era, problems of multiculturalism are inevitable, including in learning Arabic because language is a human culture, which has different characteristics in terms of race, ethnicity, religion, geography and language.Keywords: Pendidikan Multikultural, Bahasa Arab, Maḥārah al-Arbā’